2010
DOI: 10.1039/b9nj00780f
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of uniform Ag/TiO2 nanotube array structures with enhanced photoelectrochemical performance

Abstract: In the current work, pulse current deposition has been used to prepare evenly distributed and uniformly sized Ag nanoparticles on a TiO2 nanotube array photoelectrode. The Ag particle size and loading were controlled by the pulse deposition time. The Ag/TiO2 nanotube arrays were characterized by SEM, TEM, XRD, XPS and UV-vis diffuse reflection absorption. The resulting electrode contained intimately coupled, three-dimensional Ag/TiO2 structures with greatly improved photocurrent generation and charge transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
83
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(100 citation statements)
references
References 50 publications
15
83
0
2
Order By: Relevance
“…5 (a)), i.e., Ag 3d 5/2 and Ag 3d 3/2 binding energies appeared at 369 eV and 375 eV, respectively. This is in good agreement with metallic silver values [44,45]. XPS spectrum of Zn 2p (Fig.…”
Section: Experimental Procedures For Photocatalytic Degradation Of Dyesupporting
confidence: 70%
“…5 (a)), i.e., Ag 3d 5/2 and Ag 3d 3/2 binding energies appeared at 369 eV and 375 eV, respectively. This is in good agreement with metallic silver values [44,45]. XPS spectrum of Zn 2p (Fig.…”
Section: Experimental Procedures For Photocatalytic Degradation Of Dyesupporting
confidence: 70%
“…Ag 3d 5/2 peak for AgO is at 367.4 eV. 32 So, the XPS spectrum of Ag 3d in TiNT-Ag60s (Figure 4) further confirms that the nanoparticles are AgO. Both TEM and XPS results clearly show that AgO nanoparticles were on the TiNTs.…”
Section: Characterization Of Ago-deposited Tintssupporting
confidence: 52%
“…6 c) peak located at 400.4 eV could be assigned to neutral amino group -NH2 or N-H bond of amide bond present in the protein moiety [ 24,25,26 ].From the survey scan (Fig.6d) and spectrum of Ag 3d (Fig. 6 e) the binding energies of Ag 3d5/2 and Ag 3d3/2 are found to be at 368 and 374 eV, respectively[ 27,28,29,30 ].Therefore, it is concluded that the proteins were responsible for the bio-reduction of AgNO3 into AgNPs. X-ray diffraction analysis X-ray diffraction is used to assess the crystalline structure and preferred orientation in powder solid samples of the AgNPs.…”
Section: Xps Of the Silver Nanoparticlesmentioning
confidence: 99%